Thermal regime of lakes in the Polish Lowlands in the light of climate change - Skowron, Rajmund; Jaszczyk, Tomasz (Bulletin of Geography. Physical Geography Series, 2025)
Based on data on surface water temperature, summer thermal structure and ice phenomena in lakes in northern Poland for the years 1961-2020, changes in their thermal regime during the period of climate change were determined. The average annual surface water temperatures in all lakes (13 lakes) were characterized by an average positive trend at the level of 0.044oC·year-1 with 0.015 oC·year-1 in January and 0.069 oC·year-1 in May. In turn, in the summer (from 20 July to 20 August), the average water temperature within the epilimnion (to a depth of 5 m) was characterized by a positive trend at the level of 0.05–0.07 oC·year-1, while below this layer a negative trend was noted in all lakes. A characteristic feature observed in all lakes was a decrease in the thickness of the epilimnion with a trend at the level of 0.07–0.11 m·year-1. The hypolimnion layer showed a negative trend for its water temperature, which ranged from 0.02oC·year-1 (Raduńskie Górne) to 0.07oC·year-1 (Miedwie). The ice cover appeared on average in the middle of the third decade of December and its trend was characterized by negative values ​​(0.1-0.2 days∙year-1). In turn, the dates of its disappearance were recorded earlier and earlier, most often in the second decade of March. The consequence of the initial and final dates with ice cover is the length of its occurrence, which was shortened on average by 0.7-0.8 days∙year-1. The general trend of shortening the period with ice cover was also accompanied by a clear decrease in its thickness (with a trend of (0.2-0.4 cm∙year-1).